Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1161/jaha.115.002034
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term, High‐Dose Fish Oil Supplementation Increases the Production of Omega‐3 Fatty Acid–Derived Mediators in Patients With Peripheral Artery Disease (the OMEGA‐PAD I Trial)

Abstract: BackgroundPatients with peripheral artery disease (PAD) experience significant morbidity and mortality. The OMEGA-PAD I Trial, a randomized, double-blinded, placebo-controlled trial, addressed the hypothesis that short-duration, high-dose n-3 polyunsaturated fatty acids (n-3 PUFA) oral supplementation improves endothelial function and inflammation in PAD.Methods and ResultsEighty patients with stable claudication received 4.4 g of fish oil or placebo for 1 month. The primary end point was endothelial function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 83 publications
(176 reference statements)
0
93
0
Order By: Relevance
“…It has been well established that oral supplementation with omega-3 fatty acids or diets rich in their marine sources increase both plasma and cell-membrane levels of EPA and DHA (Grenon, Owens et al 2015, Wang, Hjorth et al 2015). Unfortunately, the relationship between blood levels of these n-3 fatty acids and the downstream biochemical pathways producing SPM is poorly understood.…”
Section: Translation: Resolution Pharmacology In Vascular Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established that oral supplementation with omega-3 fatty acids or diets rich in their marine sources increase both plasma and cell-membrane levels of EPA and DHA (Grenon, Owens et al 2015, Wang, Hjorth et al 2015). Unfortunately, the relationship between blood levels of these n-3 fatty acids and the downstream biochemical pathways producing SPM is poorly understood.…”
Section: Translation: Resolution Pharmacology In Vascular Injurymentioning
confidence: 99%
“…The physiological impact of oral supplementation of n-3 PUFA for each individual is variable depending on baseline characteristics such as prior dietary intake and hereditary metabolic factors (von Schacky 2014). Recently, the OMEGA-PAD-I Trial demonstrated the effects of short-term n-3 fatty acid supplementation on altering biochemical SPM pathways in PAD patients (Grenon, Owens et al 2015). In this study, eighty subjects were randomized to either 4.4g of fish oil, corresponding to 2.6g of EPA and 1.8g of DHA daily, or placebo for one month.…”
Section: Translation: Resolution Pharmacology In Vascular Injurymentioning
confidence: 99%
“…Subsequent studies have examined the effect of n-3 fatty acids supplementation in relation to plasma SPM formation in healthy volunteers [21,23 & ,26]; patients suffering from chronic headaches [22]; mild hypertriglyceridemia [27]; chronic renal disease [24 && ]; and peripheral artery disease [28].…”
Section: Specialized Proresolving Mediators In Humans and The Effect mentioning
confidence: 99%
“…The effect of n-3 fatty acid supplements on SPMs and other lipid mediators was studied in 80 patients with peripheral artery disease [28]. The study was a randomized double blind trial that gave patients either 4.4 g/day n-3 fatty acids or placebo for 1 month with endothelial function as the primary outcome [28].…”
Section: Specialized Proresolving Mediators In Humans and The Effect mentioning
confidence: 99%
See 1 more Smart Citation